Blood lactate as a predictor of clinical outcomes and health-care resource needs in combat abdominal injuries - І.В. Собко; О.В. Рабощук; А.В. Верба; С.А. Асланян; Г.П. Хитрий; В.М. Мошківський; І.П. Кураченко; Т.С. Бордюг (Медицина неотложных состояний, 2024)
Background. Combat abdominal injuries (CAI) are characterized by high mortality and occupy a leading position among the issues of battlefield surgery. It is very important to evaluate early and accurately the severity of CAI, which will allow starting correct treatment in time, preventing possible complications and improving clinical outcomes. The low sensitivity of commonly used cardiovascular parameters to detect the initial manifestations of tissue hypoperfusion induced by blood loss dictates the need to use more effective markers that reflect metabolic changes in tissues. The aim of this study is to determine the predictive efficacy of serum lactate regarding the risk of death and health-care resources needs in patients with CAI. Materials and methods. We examined 86 injured servicemen with CAI who were randomized into two groups — survivors and nonsurvivors. The predictive efficacy of capillary blood lactate and its clearance regarding the risk of death and health-care resource needs in CAI were studied. Six consecutive (within 48 h) measurements of lactate and lactate clearance corresponding to each measurement (except the first) were evaluated for each patient. Logistic regression models were constructed and analyzed to assess the influence of lactate level and lactate clearance on the risk of death and need for vasopressor support during medical evacuation to the Role 3 (after performing an emergency surgery). A correlation analysis was conducted on the association between lactate and the need for RBC transfusion, as well as assessment of the CAI severity using the Admission Trauma Score (AdTS). Results. In the group of nonsurvivors, lactate was higher (p = 0.001) at all stages of the study. We determined that an increase in the lactate level at the time of admission of a victim with CAI to the forward surgical team (LacpreOP) increased the risk of death by 1.5 times for every 1 mmol/l of lactate elevation (odds ratio (OR) 1.5, 95% confidence interval (CI) 1.22–1.85), and the chances of the need for vasopressor support during medical evacuation to the Role 3 — by 1.7 times for every 1 mmol/l of lactate elevation (OR 1.7, 95% CI 1.05–1.86). A strong positive correlation (ρ = 0.8) was found between LacpreOP and the need for RBC transfusion during the first 24 h after injury, as well as a moderate positive correlation (ρ = 0.5) between LacpreOP and CAI severity assessment on the AdTS. Conclusions. The results of the study indicate the high predictive efficacy of lactate regarding the risk of death (OR 1.5, 95% CI 1.22–1.85) and the need for vasopressor support during medical evacuation of victims with CAI to the Role 3 (OR 1.7, 95% CI 1.05–1.86). There was a positive correlation between lactate and the need for RBC transfusion during first 24 h after injury (ρ = 0.8), as well as between lactate level and CAI severity according to the AdTS (ρ = 0.5).